2017
DOI: 10.1016/j.eats.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Iliotibial Band Lengthening: An Arthroscopic Surgical Technique

Abstract: Iliotibial (IT) band syndrome is a common cause of lateral knee pain in runners and cyclists. Many can be treated nonoperatively; however, some may require surgical lengthening of their IT band to achieve optimal pain relief and a return to preinjury level of activity. Several studies have been published detailing surgical lengthening procedures and satisfactory outcomes after these procedures. However, it is important to continue to improve on and optimize outcomes. We present our arthroscopic IT bandelengthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…However, none of the previous studies used a combined arthroscopic technique for sub-iliotibial release and elongation of the ITB, representing global management of ITBS. Pierce et al (20) described a combined technique adding arthroscopic lengthening of the ITP through incisions with Metzenbaum scissors at proximal, distal, anterior and posterior level of the ITB, from its point of insertion in Gerdy's tubercle. However, to our knowledge, no previous studies have evaluated the results of arthroscopic management combining both techniques in a prospective series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the previous studies used a combined arthroscopic technique for sub-iliotibial release and elongation of the ITB, representing global management of ITBS. Pierce et al (20) described a combined technique adding arthroscopic lengthening of the ITP through incisions with Metzenbaum scissors at proximal, distal, anterior and posterior level of the ITB, from its point of insertion in Gerdy's tubercle. However, to our knowledge, no previous studies have evaluated the results of arthroscopic management combining both techniques in a prospective series of patients.…”
Section: Discussionmentioning
confidence: 99%
“…14,30 There is an expansion of arthroscopic techniques reported to address ITBS, but they were excluded from our systematic review due to failure to report patient outcomes. [30][31][32] There is an expansion of arthroscopic techniques reported to address ITBS, but they were excluded from our systematic review due to failure to report patient outcomes [30][31][32] The comparison of the clinical outcomes and safety profile between open and arthroscopic surgical techniques to address ITBS is a subject of future investigation. In contrast to the group of studies reporting the outcomes following conservative management of ITBS, the return to sport rate, timing, and level of competition upon return was more consistently reported in studies that examined the effectiveness of surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The disorder was formerly known as "runner's knee" because it was the most common cause of lateral knee pain in runners 3 , with an incidence of 1.6-14%. Interestingly, many sports including repetitive cyclic movements of the knee are known to lead to the same pain syndrome, including cycling (15-24%), soccer, tennis, and competitive rowing 1,4,5,6,7,8,9 . Inappropriate training and sudden changes in training schedules such as excessive increase in distance or hill running exacerbate the complaints 10 .…”
Section: Introductionmentioning
confidence: 99%
“…(i) As the name of the syndrome states, it was thought that repetitive friction of the ITB along the lateral femoral epicondyle would lead to an inflammatory response with oedema, and potential chronicity due to fibrosis, cicatrisation, neovascularization and -innervation 1,3,7,9,11,12,13 . (ii) Fairclough et al studied 15 cadavers and found a firm distal attachment of the ITB over the linea aspera, preventing its anteroposterior movement 14 .…”
mentioning
confidence: 99%